Assessment on the decolourization of textile dye (Reactive Yellow) using Pseudomonas sp. immobilized on fly ash: Response surface methodology optimization and toxicity evaluation. (1st October 2018) - Roy, Uttariya; Sengupta, Shubhalakshmi; Banerjee, Priya; Das, Papita; Bhowal, Avijit; Datta, Siddhartha
Abstract: This study focuses on the investigation of removal of textile dye (Reactive Yellow) by a combined approach of sorption integrated with biodegradation using low cost adsorbent fly ash immobilized with Pseudomonas sp. To ensure immobilization of bacterial species on treated fly ash, fly ash with immobilized bacterial cells was characterized using Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), and fluorescence microscopy. Comparative batch studies were carried out using Pseudomonas sp, fly ash and immobilized Pseudomonas sp on flyash and were observed that immobilized Pseudomonas sp on flyash acted as better decolourizing agent. The optimized pH, temperature, and immobilized adsorbent dosage for highest percentage of dye removal were observed to be pH 6, 303 K, 1.2 g/L in all the cases. At optimum condition, the highest percentage of dye removal was found to be 88.51%, 92.62% and 98.72% for sorption (flyash), biodegradation ( Pseudomonas sp) and integral approach ( Pseudomonas sp on flyash) respectively. Optimization of operating parameters of textile dye decolourization was done by response surface methodology (RSM) using Design Expert 7 software. Phytotoxicity evaluation with Cicer arietinum revealed that seeds exposed to untreated dye effluents showed considerably lower growth, inhibited biochemical, and enzyme parameters with compared to those exposed to treated textile effluents. Thus this immobilized inexpensive technique could be used for removal of synthetic dyes present in textile wastewater. Highlights: Pseudomonas mendocina was immobilized on waste and processed fly ash. The immobilized Pseudomonas sp. was used to remove Reactive Yellow by integrated sorption and biodegradation approach. Dye removal was found to be 88.51%, 92.62% and 98.72% for sorption, biodegradation and integrated approach. Optimization of operating parameters of was done by response surface methodology. Cicer arietinum seedlings exposed to untreated effluents showed poor growth, inhibited biochemical and enzyme parameters.